Certain hormonal profiles of postpartum anestrus jersey crossbred cows treated with controlled internal drug release and ovsynch protocol - Dayanidhi Jena (Veterinary World, 2016)
Aim: The study was conducted to determine the serum levels of certain hormones in post-partum anestrus cows following treatment with controlled internal drug release (CIDR) and Ovsynch protocol. Materials and Methods: A total of 30 postpartum anestrus cows were divided into three equal groups after thorough gynecoclinical examination. The Group 1 animals received an intravaginal progesterone device on day 0 and 2 ml of prostaglandin F2α (PGF2α) on day of CIDR removal (7th day), Group 2 cows were treated with ovsynch protocol (gonadotropinreleasing hormone [GnRH]-PGF2α-GnRH) on day 0, 7 and 9, respectively, and Group 3 cows were supplemented with mineral mixture and treated as control. The serum estrogen, progesterone, triiodothyronine, and thyroxine concentration were estimated using enzyme-linked immunosorbent assay kit and absorbance was read at 450 nm with Perkin Elmer Wallac 1420 Microplate Reader. Results: There was a significant increase in progesterone level in Group 1 after withdrawal of CIDR as compared to other two groups. However, the estrogen assay revealed a greater concentration in Group 2 against Group 1 on day 7 of sampling. However, there was no significant difference for serum triiodothyronine (T3) and thyroxine (T4) irrespective of treatment protocols and days of sampling. Conclusion: Treatment with CIDR based progesterone therapy and drug combinations may affect the reproductive hormonal balance like estrogen and progesterone, which is inevitable for successful return to cyclicity and subsequent fertilization and conception. However, as far as serum T3 and T4 concentration concerned it may not give an astounding result.